Relationship Between Menstrual Cycle and Anemia in Adolescent Girl at MA Nurul Islam Mataram - Aswandani, Alifa; Danianto, Ario; Cholidah, Rifana (Jurnal Biologi Tropis, 2024)
Adolescent are individuals who experience rapid growth and development process. In adolescent girl in particular, there is a physiological process occurs called menstruations that caused bleeding every month in adolescent girl and known as menstrual cycle. As a result of the menstruation, young women become a vulnerable group to anemia. This study intends to determine the relationship between the menstrual cycle and the incidence of anemia in adolescent girl at MA Nurul Islam Mataram. This study is quantitative categorical analysis with a cohort retrospective approach. The sample in this study was 48 young women at MA Nurul Islam Mataram, divided into 24 people in the normal menstrual cycle group and 24 people in the abnormal menstrual cycle group. Sample selection was carried out using a consecutive sampling method that fulfilled the sample inclusion and exclusion criteria. Data analysis in this study was carried out using the chi-square test to see the relationship between the menstrual cycle and the incidence of anemia in adolescent girl at MA Nurul Islam Mataram. The result of this study data analysis using the chi-square hypothesis test obtained a p-value of 0.505 (p<0.05) which shows that there is no significant relationship between the menstrual cycle and the incidence of anemia in young women at MA Nurul Islam Mataram.